2009
DOI: 10.1111/j.1439-0426.2008.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight and length-length relationships of 10 small fish species from the Ganges, Bangladesh

Abstract: SummaryThis study describes the length-weight (LWR) and lengthlength (LLR) relationships for ten small indigenous fish species from the lower part of the Ganges, Bangladesh, namely Ailia coila, Amblypharyngodon mola, Aspidoparia morar, Clupisoma atherinoides, Eutropiichthyes vacha, Glossogobius giuris, Gudusia chapra, Lepidocephalus guntea, Mystus vittatus, and Puntius ticto. A total of 2142 specimens, representing 10 species of 5 families used for this study were caught by traditional fishing gear from March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 4 publications
7
57
6
Order By: Relevance
“…In the present study it was observed that there existed positive linear relationship in all the cases of the relationships between total length with different body length of Rita rita. The correlation of LLRs in the present study is similar to the findings of Hossain et al (Hossain,2010); Clupisoma atherinoides (Hossain et al,2009), Heteropneustes fossilis in the Ganges and Mystus cavasius (Venkateshwarlu et.al. ,2007) from Bhadra reservoir, Karnataka.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study it was observed that there existed positive linear relationship in all the cases of the relationships between total length with different body length of Rita rita. The correlation of LLRs in the present study is similar to the findings of Hossain et al (Hossain,2010); Clupisoma atherinoides (Hossain et al,2009), Heteropneustes fossilis in the Ganges and Mystus cavasius (Venkateshwarlu et.al. ,2007) from Bhadra reservoir, Karnataka.…”
Section: Discussionsupporting
confidence: 81%
“…Size relationships are either between any two linear dimensions or between length and weight measurements. These relationships have several applications in fisheries biology, including: (i) the estimation of weight from length for individual fish and calculation of stock biomass (Anderson and Gutreuter 1983;Petrakis and Stergiou 1995;Martin-Smith 1996); (ii) conversion of growth-in-length to growth-in-weight for the prediction of weight-at-age equations and use in stock assessment models (Pauly 1993); (iii) calculation of condition indices (Anderson and Gutreuter 1983;Petrakis and Stergiou 1995); (iv) comparisons of life history and morphology of populations from different regions (Safran 1992;Petrakis and Stergiou 1995);and (v) comparison of length-length relationships (LLRs) for comparative growth studies (Moutopoulos and Stergiou 2002;Hossain et al 2006a;2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is also inferred that higher b values indicates relatively productive environmental conditions (Gopakumar et al, 1991) and if so LWR data appear to reflect the poor growing condition of the fish in these waters. Many factors could contribute to the differences of growth of fish such as difference of habitat, fish activities, food habits and seasonal growth rates (Hossain et al, 2009). Other factors such as temperature, trophic level and food availability in the community were also important.…”
Section: Discussion a Length-weight Relationshipmentioning
confidence: 99%